Optimization of a new artemisinin-based combination therapy of artesunate-piperaquine fixed-dose combination tablet with enhanced in vivo antimalarial effects - Van Han Nguyen, Trong Bien Tran, Ngoc Bao Tran, Viet Hoang Nguyen, Quang Anh Luong,, Thi Tien Nong (Journal of Applied Pharmaceutical Science, 2023)
This work aimed to develop a new fixed-dose combination tablet (FDCT) containing artesunate (ART) 50 mg and piperaquine 320 mg for enhanced malaria parasites treatment. Firstly, the physico-chemical properties of ART were improved effectively by forming solid dispersions (SDs) with β-cyclodextrin. Secondly, the FDCT was prepared by direct compression method using ART SDs and piperaquine phosphate (PQP). The formulation was experimented with full factorial design and optimized by Modde 5.0 software. FDCT were assessed for physical properties, drug content assay, dissolution, stability, acute toxicity, and in vivo antimalarial efficacy. ART and PQP assays were performed by using the validated high-performance liquid chromatography and UV spectrophotometry methods. Dissolution tests were conducted as per US Pharmacopoeia version 43 (USP43). The in vivo antimalarial activity of ART-PQP FDCT was assessed on mice infected with chloroquine-resistant Plasmodium berghei. The obtained FDCT met all desirable physical properties with an average weight of 670 mg, weight variation range of 690.5–702.9 mg per tablet, hardness range of 64-68N, friability of 0.5%–0.6%, and disintegration of 7–8 minutes. The contents of ART and PQP per tablet were 51.3–52.6 mg and 322.1–330.8 mg, respectively. The dissolution of ART and PQP within 30 minutes were more than 90% and 80%, respectively. Acute toxicity was identified with LD50 value in mice of 1,550.5 mg/kg. The cure rate of FDCT on mice of 93.3% was distinctly higher than that of single ART or PQP. The new ART-PQP FDCT showed enhanced antimalaria activity over monotherapies against chloroquine-resistant Plasmodium berghei.